Engajamento de stakeholders e desempenho: estudo de caso de política pública municipal de educação - Aragão, Paula Balardin Ribeiro (2021)
This research sought to analyze what is the relationship between different levels of stakeholder engagement and the performance of the municipal education public policy "COMDECampo" of Cachoeira do Sul - RS? As specific objectives, it was established: i) to map the stakeholders of the municipal public policy of education; ii) to verify the perception of stakeholder groups in relation to levels of engagement; iii) to evaluate how levels of engagement affect the perception of policy performance; iv) to propose strategies to improve stakeholder engagement. This is a case study, with a quantitative approach. The stakeholders of the municipal public policy of education were mapped, applying the questionnaire prepared by the author based on the study by Bowen et al. (2010) that proposes engagement on three levels: transactional, transitional and transformational, consisting of 24 statements related to public policy, on a 5-point Likert scale. The survey considered the fourteen rural schools in the municipality, which resulted in a sample of 60 respondents, being principals, teachers, and public policy members. The statistical tests of Kruskall-Wallis, Correlation, and Multiple Linear Regression showed, mainly by the increasing coefficients of R2 (32%, 37%, and 44%) that engagement not only affects the stakeholders' perception of performance, but this perception also increases as the level of engagement increases. It was also possible to observe that different stakeholder groups have different perceptions of engagement levels, which allows us to understand which type of strategy is most appropriate. In addition, the research proposes some stakeholder engagement strategies, demonstrating the importance of stakeholder engagement for the success of a public policy.